Prognostic value of haptoglobin and ceruloplasmin levels determined in cows with adhesive and nonadhesive traumatic reticuloperitonitis - Enes AKYÜZ; Uğur AYDIN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2022)
Th e aim of this study was to compare haptoglobin, ceruloplasmin, some macro mineral levels and hematological parameters in cow with adhesive and non-adhesive traumatic reticuloperitonitis (TRP). For this purpose, 20 cow with adhesive TRP constituted group 1 (G1), 20 cow with non-adhesive TRP constituted group 2 (G2), and 20 healthy cow formed the control group (C). Blood samples were taken from cow with clinical suspicion of TRP, and the infl ammation status was examined by performing the glutaraldehyde test. As a result of radiographic inspection, it was decided to perform rumenotomy for the cows determined that the foreign body had penetrated the reticulum. Th e cows were divided into groups according to the presence or absence of adhesion during the rumenotomy. Total leukocyte count was found to be signifi cantly higher in G1 compared to G2 and C. Calcium, magnesium, phosphorus and albumin were found to be signifi cantly lower in G1 and G2 compared to the C (P<0.05). Haptoglobin and ceruloplasmin were determined to be at the highest level in G1 compared to the other groups (P<0.05). In this study, detection of positive acute phase proteins with higher levels of G1 and lower levels of albumin was found to be important. In conclusion, we think that these parameters will provide important information in determining the presence of adhesion in cows with TRP. In addition, according to the information obtained from the cow owners aft er rumenotomy, it was learned that the general health status of the cows in G1 was distressed. In the light of these data, the relevant parameters before rumenotomy can give an idea for prognostic evaluation in TRP.